AI Integration in Telemedicine: Revolutionizing Virtual Healthcare Delivery - Dr. Rohith Vangalla, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article explores the transformative impact of Artificial Intelligence integration in telemedicine services, highlighting its pivotal role in revolutionizing virtual healthcare delivery. The article examines various dimensions of AI applications in healthcare, including real-time data analysis, remote patient monitoring systems, patient engagement platforms, operational efficiency improvements, clinical benefits, and future developments. The article reveals significant advancements in diagnostic accuracy, patient care personalization, and healthcare accessibility through AI-powered solutions. The article demonstrates how AI integration has enhanced clinical decision-making processes, streamlined administrative workflows, and improved patient outcomes across diverse healthcare settings. Furthermore, it addresses the critical role of AI in reducing healthcare disparities by extending quality medical services to underserved communities through telemedicine platforms. The article also evaluates the economic implications of AI implementation in healthcare systems, examining both immediate operational benefits and long-term cost efficiencies. This article analysis provides valuable insights into the synergistic relationship between AI and telemedicine, establishing a framework for understanding their combined potential in shaping the future of healthcare delivery.
Keywords: Artificial Intelligence; Telemedicine; Healthcare Innovation; Patient Monitoring Systems; Clinical Decision Support